IMPLEMENTASI MEDIA MAGIC STAIRS 3 DIMENSI PADA MATERI SATUAN PANJANG TERHADAP HASIL BELAJAR SISWA KELAS 3 DI UPPT SDN 02 TANJUNGSARI KOTA BLITAR - Khusnia, Lia; Shofi Nur Amalia; Ragil Tri Oktaviani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Students' low understanding can result in learning outcomes that are not maximized in learning, therefore the purpose of this study is to implement 3-Dimensional Magic Stair media on student learning outcomes. This research includes Classroom Action Research (PTK) which consists of 4 stages, namely the planning stage, the implementation stage, the observation stage, and also the reflection stage. Researchers conducted research with II cycle steps and each cycle consisted of 2 meetings. Researchers used several data collection techniques, including: observation, interviews, tests and documentation. This research was conducted in class 3 UPT SDN 02 Tanjungsari Blitar City. The result of this study is a significant increase in student learning outcomes in math unit length. In addition to the increase in learning evaluation results, there was a percentage of students who touched the KKM score from 58.3% in pre-action to 70.8% in cycle I and ended in cycle II with a percentage of 87.5%.